2019
DOI: 10.1039/c9cc02537e
|View full text |Cite
|
Sign up to set email alerts
|

Small-pore CAU-21 and porous PIM-1 in mixed-matrix membranes for improving selectivity and permeability in hydrogen separation

Abstract: Very selective and permeable membranes for hydrogen separation have been fabricated by hybridizing CAU-21 MOF with a small aperture and PIM-1 polymer with high porosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the case of MMMs for H 2 separation, selection of MOFs with relatively small pore size is required to obtain a size sieving effect due to the small molecular size of H 2 (kinetic diameter 0.29 nm). 103 Recently Zhu et al reported MMMs with CAU-21-ODB (pore size ∼0.33 nm) with PIM-1 as a polymer matrix. 103 Uniform CAU- 105 In contrast, the pristine polyimide membrane that displayed H 2 /CO 2 selectivity and H 2 permeability of 1.8 and 220, respectively.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of MMMs for H 2 separation, selection of MOFs with relatively small pore size is required to obtain a size sieving effect due to the small molecular size of H 2 (kinetic diameter 0.29 nm). 103 Recently Zhu et al reported MMMs with CAU-21-ODB (pore size ∼0.33 nm) with PIM-1 as a polymer matrix. 103 Uniform CAU- 105 In contrast, the pristine polyimide membrane that displayed H 2 /CO 2 selectivity and H 2 permeability of 1.8 and 220, respectively.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…103 Recently Zhu et al reported MMMs with CAU-21-ODB (pore size ∼0.33 nm) with PIM-1 as a polymer matrix. 103 Uniform CAU- 105 In contrast, the pristine polyimide membrane that displayed H 2 /CO 2 selectivity and H 2 permeability of 1.8 and 220, respectively. The study suggests that MOF selection is crucial to further improve the separation capabilities of MMMs.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs have been widely investigated in recent years as some of the most promising materials due to their stable frameworks. Some aluminum MOFs, including MIL-53 [ 91 , 92 ], MIL-96 [ 93 ], NH2-MIL-101 [ 94 , 95 ], CAU-21-ODB [ 96 ] and NH2-MIL-53 [ 94 , 97 ], are incorporated into polymer matrices. The successfully application of various aluminum MOFs such as DUT-5 [ 98 ], CAU-1 [ 99 ] and MIL-53 [ 100 ] in MMMs contributes into flux increment in the pervaporation study.…”
Section: Mixed Matrix Membranesmentioning
confidence: 99%
“…At relatively low filler loadings (1 wt %, 2 wt %), FCTF-1 nanoparticles disperse uniformly within the PIM-1 matrix, similar to other systems. 47 This is due to the organic nature and small size of the FCTF-1 nanoparticles.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%